Bio-Mechanical Pulping of Bacteria Pre-Treatment on Oil Palm Biomass for Handsheet Production - Mutia Syarifah, Sharfina; Sari Mohd Kassim, Angzzas; Mohd Aripin, Ashuvila; Ishak, Nadiah; Fadilat, Ayeronfe; Adnan, Sharmiza (International Journal of Engineering and Technology, 2019)
Biopulping is one of the alternative process towards conventional process; chemical and mechanical processes. The biopulping process in this study was delignification using the bacteria Bacillus sp. which were isolated from the Coptotermes curvignathus gut (termite insects). The research was explored to determine the best performance of the bacteria species on the oil palm biomass in handsheet production. The bio pulp was produced by biopulping under submerged fermentation using luria broth (LB) at pH 6.5, 35Â°C for 7 days. The bio pulp samples were grinded using refiner mechanical pulping (RMP) which were sieved through 200 Âµm, furthermore proceeded with the handsheet production according to technical association pulp and paper industry (TAPPI) standard method. The characterization of handsheet physical properties were analysed on tensile, bursting, tearing, brightness and opacity. From this result, EFB treated shows better performance in mechanical strength with low grammage value of 48.952 g/m2, 637.3 Âµm thickness average, 7.144 Nmâ„g tensile index, 1.6850 Mn.m2/g tearing index and 0.346 kPa.m2/g of bursting index. Therefore, this bacteria shown to be an alternative process for greener and environmental friendly production of pulp and paper industry and the non-wood empty fruit bunch of oil palm have greater potential in replacing wood resources.Â Â